LEADERSHIP OF SCHOOL PRINCIPLES IN INCREASING STUDENTS' LEARNING MOTIVATION FOR ONLINE-BASED FINAL EXAMS AT SMP NEGERI 1 KOTA SIGLI - Hartini; Siti Mayang Sari; Akmaluddin; Muhammad Kaulan Karima (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Principal leadership has an important role in increasing student motivation toface online-based final exams, because it greatly influences the progress ofstudents and schools, because the lack of motivation of students to prepare foronline-based final exams makes the achievements achieved by students of SMPNegeri 1 Sigli City often decreased. The purpose of this study was to determinethe principal's leadership in increasing student learning motivation in facingonline-based final exams, the principal's leadership strategy in increasingstudent learning motivation in facing online-based final exams and theconstraints of students' learning motivation in facing online-based exams. Thistype of research is descriptive qualitative research. Observation data collectiontechniques, interviews, and documentation. The subjects of this study wereschool principals, teachers and students. The results showed that the principal'sleadership strategy in increasing students' learning motivation in facing onlinebased final exams was carried out by providing various learning facilities andinfrastructure, asking teachers to familiarize students with learning to answerprevious year's exam questions, providing special study hours online-basedexam methods and holding extra hours in the afternoon. Obstacles facingonline-based exams are the limited support facilities for online-based exams,the lack of student awareness and the lack of support from students' families